Production of desert rose seedlings under different cultivation techniques - Ferreira Moraes, Lídia; Sara Teixeira de Oliveira, Paula; Santos Da Silva Veras, Amália; Yuri Ferreira Pereira, Ramón; Veras Cordeiro, Kleber; Ferreira dos Santos, Janaiane; Dias de Oliveira Neto, Edson; Rachel Salustriano da Silva-Matos , Raissa (Comunicata Scientiae, 2023)
Desert roses have gained notoriety in the ornamental market; however, the use of locally produced substrates is diverse. Three experiments were carried out using a completely randomized design, with treatments arranged in a 3x4 factorial. Physical and chemical analyses were carried out for the following substrates: carnauba bagana, carbonized rice husk, decomposed babassu stem, and soil. Experiment 1: three sowing depths, D1: 0mm, D2: 5mm and D3: 10 mm, combined with four substrates. Experiment 2: three substrates combined with four shading screens: thermal reflector, white shading, black shading and open sky. Experiment 3: three substrates combined with four irrigation levels: 100, 75, 50, and 25%. Measurements were made in the three experiments and data were tested by analysis of variance using the “F” test, at the levels of 1% and 5%. Regression and averages were explored using Tukey’s test. It was concluded that the seedlings developed better under a level of 10 mm and substrate with 100% carnauba bagana, in association with an outdoor environment, and water levels between 50 and 75% of pot capacity.